Left isomerism with bilateral superior vena cava, interrupted inferior vena cava and tetralogy of Fallot - Nikhil Bansal; Rajarshi Ghosh; Lakshmi Kumari Sankhyan; Sujoy Chatterjee; Srirup Chatterjee; Satyajit Bose (Wolters Kluwer Medknow Publications, 2020)
The association of left isomerism with tetralogy of Fallot (TOF) is rare and reported as scattered case reports. Complex congenital cardiac and noncardiac malformations are known to be associated with left isomerism, but right-sided obstructive lesions are rare. We present our experience with a case of left isomerism with bilateral superior vena cava, interrupted inferior vena cava, and TOF managed by atrial septation and intracardiac repair.